Perinatal mortality. Experience in the San Bartolome Hospital. Ten years later - Urquizo, Raúl (2015)
OBJETIVE. To determine 1995 perinatal mortality rate and compare with findings ten years before. DESIGN. Transversal retrospective and descriptive study. RESULTS. In 5249 clinical histories 70 perinatal deaths were found,with a perinatal mortality rate of 13,3%. Preterm deliveries have increased from 43% (1985) to 6,7% (1995) as well as very low weight <1500 g from 0,99% (1985) to 1,1% (1995), without increase in perinatal mortality. Pathology has also changed and first cause of death is now congenital anomalies in 26,04%, displacing severe asphyxia, the first cause of death in 1985. The majority of deaths was in patients without prenatal control (75,7%). CONCLUSION. Exclusive breastfeeding, early mother-infant lodging, Kangaroo method for premature babies and capacitation of hospital personnel in neonatal reanimation has reduced perinatal mortality rate along these 10 years. If we wish to decrease it further, we will have to insist in prenatal con-trol, perinatal technologies and risk focusing.